Kondycja moralna społeczeństwa polskiego w kontekście demonstratywnych i kompensacyjnych zachowań konsumenckich. - Adamczyk, Grzegorz (Acta Universitatis Lodziensis. Folia Sociologica, 2012)
Pursuant to the concept developed by Helmut Klages, five types of morality characteristic for contemporary societies with developed economic structures may be distinguished: conventional, realistic, idealistic, hedonistic-materialistic morality and morality of the resigned. In compliance with the thesis of this paper, the latter two types of morality should be significantly connected with irrational consumer behaviours – demonstrative consumption, compensative consumption and shopaholism. As our research conducted throughout Poland in August 2010 demonstrated, approximately 1/5 of Poles aged 15 and more are included in the segments of hedonisticmaterialistic morality and of morality of the resigned. As expected, the highest percentage of compensative shoppers was found in the segment of hedonistic materialists – 1/3 of them buy compensatively, whereas 1/3 of hedonistic materialists buying compensatively demonstrate inclinations to shopaholism. The idealists constitute the second most susceptible to compensation segment. Moreover, this segment leads as well in terms of demonstrative consumer behaviours.